2004
DOI: 10.1128/jb.186.17.5661-5671.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of afpA , a Gene Encoding an Antifreeze Protein from the Arctic Plant Growth-Promoting Rhizobacterium Pseudomonas putida GR12-2

Abstract: The Arctic plant growth-promoting rhizobacterium Pseudomonas putida GR12-2 secretes an antifreeze protein (AFP) that promotes survival at subzero temperatures. The AFP is unusual in that it also exhibits a low level of ice nucleation activity. A DNA fragment with an open reading frame encoding 473 amino acids was cloned by PCR and inverse PCR using primers designed from partial amino acid sequences of the isolated AFP. The predicted gene product, AfpA, had a molecular mass of 47.3 kDa, a pI of 3.51, and no pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 80 publications
1
38
0
Order By: Relevance
“…The proteins are known as antifreeze proteins (AFPs) or antifreeze glycoproteins (AFGPs). 1 Thus far, these proteins have been found in various species of fish, 2-4 insects, [5][6][7] bacteria 8,9 and plants 10,11 (hereafter, AFPs and AFGPs are collectively referred to as AFPs).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins are known as antifreeze proteins (AFPs) or antifreeze glycoproteins (AFGPs). 1 Thus far, these proteins have been found in various species of fish, 2-4 insects, [5][6][7] bacteria 8,9 and plants 10,11 (hereafter, AFPs and AFGPs are collectively referred to as AFPs).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of polar psychrophiles have revealed adaptations such as lipid modification to maintain membrane fluidity, accumulation of polyols, genome adaptations, and production of cold shock proteins and cold-active enzymes, including enzymes important for protein synthesis (4,9,19,24,26). Although it has been argued that polar bacteria do not require antifreeze proteins (AFPs) when they are living at the junction of ice crystals (9,13,20), the accumulation of molecules that inhibit ice recrystallization (IR) could be part of an adaptive response in Arctic and Antarctic microbes (12,17,18,22,27,33). In contrast, certain Pseudomonas species have ice-nucleating protein complexes that promote the growth of ice (19) or cold acclimation proteins that are believed to contribute to freeze tolerance (23).…”
mentioning
confidence: 99%
“…strain C14, also showed IR inhibition. IR inhibition can be mediated by polysaccharides, such as xanthan gum, that are used commercially to prevent the formation of large ice crystals in ice cream or by AFPs that have been reported in a few bacteria, such as an Antarctic Moraxella (34), an Arctic Rhizobacterium (14,22,30,33), cold-acclimated Micrococcus and Rhodococcus (10), and Antarctic lake bacteria (12). For the soil isolate examined here, it is likely that the effect on ice crystals was mediated by a protein, since the activity was destroyed when the cultures were treated with a protease.…”
mentioning
confidence: 99%
“…putida isolated from the Canadian Arctic is a peculiar strain capable of proliferating at low temperatures (5°C) and able to survive freezing temperatures (−20 and −50°C), without the aid of cryoprotectants. P. putida GR12-2 could express AfpA, an antifreeze protein, and nucleation activity simultaneously (Sun et al 1995;Muryoi et al 2004). Besides, the bacterium could survive long-term in the environment (Molina et al 2000).…”
Section: Discussionmentioning
confidence: 99%